The Economic Impact of Dreamland Existence on Community in Ajibarang - Andy Widi Astuti (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2017)
This research aimed to analyze the average employee and trader income before and after working at Dreamland, decent living needs of employee and trader, and consumption needs of Dreamland employee and trader. Data of this research was primary data analyzed using t test to two correlated samples. The results of this research indicated that the employee and trader incomes were different before and after working at Dreamland and indicating an increase, employee and trader income can fulfill decent living needs, employees’ income can fulfill their consumption needs, and traders income can fulfill their consumption needs. The suggestion for the owner of Dreamland is to develop tourism activities so as to open job and business opportunities for the surrounding community, and the local government should supervise and develop tourism business by facilitating business licensing.Keywords: Economic Impact, Dreamland Tourism Object, Paired Sample t Test, Decent Living Needs, Consumption.